Evaluation of the growth, enzymatic activity, electrolyte leakage, and phytoremediation efficiency of Conocarpus erectus under cadmium and lead stress - El-Mahrouk, El-Sayed Mohamed; Eldawansy, Shereen Mostafa; El-Tarawy, Ahmed Mohamed; Ebrahim, Hayam Mohamed Aly; Eisa, Eman Abdelhakim; Tilly-Mándy, Andrea; Honfi, Péter (Frontiers in Plant Science, 2024)
Contamination of agricultural soil by heavy metals poses a significant threat to soil quality and crop yields. Using plants as a natural remediation approach attracts researchers' attention around the world. A 16-month pot experiment was conducted using Conocarpus erectus in a randomized complete block design. The growth, enzymatic activity, electrolyte leakage, and remediation potential were estimated under Cd nitrate ]40 low (L), 60 medium (M), 80 high (H) mg/kg soil [ and Pb nitrate ]400 (L),700 (M), 1000 (H) mg/kg soil[ applied individual and combinations. C. erectus demonstrated a good tolerance (over 70%) against lower and medium cadmium (Cd) and lead (Pb) levels and a medium resistance against high Cd and Pb levels, with survival of 100% under all used treatments. The most negative treatment on the growth traits and C. erectus tolerance was (H) Cd (H) Pb, which reduced plant height, chlorophyll index, dry weights of leaves, stems, and roots, root length, and tolerance index of biomass and roots by 25.